Effect of a fast‐moving tropical storm Washi on phytoplankton in the northwestern South China Sea. Issue 4 (26th April 2017) - Zhao, Hui; Pan, Jiayi; Han, Guoqi; Devlin, Adam T.; Zhang, Shuwen; Hou, Yijun
Abstract: Tropical cyclones may augment nutrients in the ocean surface layer through mixing, entrainment, and upwelling, triggering phytoplankton blooms in oligotrophic waters such as the South China Sea (SCS). Previous studies focused mainly on responses of marine environments to strong or slow‐moving typhoons in the SCS. In this study, we analyze variations of chlorophyll a (Chl a ) and oceanic conditions in the continental shelf region east of Hainan Island during the fast‐moving tropical storm Washi and investigate its influences on phytoplankton bloom and related dynamic mechanisms. Results indicate that there was significant variation of Chl a concentration in the continental shelf region, with low values (about 0.1 mg m −3 ) before the storm and a 30% increase after the storm. This increase was spatially variable, much larger nearshore than offshore. Power spectral analysis of Acoustic Doppler Current Profiler (ADCP) data at a shelf site near the study region reveals strong near‐inertial oscillations (NIOs) in the upper layer, with a period of about 36 h, close to the local inertial period. The NIOs intensified mixing and modified the stratification of the upper layer, inducing uplift of nutrients and Chl a into the mixed layer from below, and leading to surface Chl a increase. The relatively shallow nutricline and thermocline in the continental shelf region before the storm were favorable for upwelling of nutrients and generation of NIOs. Advection of nutrients from enhanced runoff during and after the storm may be responsible for the larger increase of the Chl a nearshore. Plain Language Summary: This study is exploring the dynamics of a weak‐fast‐moving tropical storm (TS) (Washi) (TSW) in inducing Chl a blooms. The major dynamic mechanism for inducing the phytoplankton bloom by the TSW in the shelf region could be different from that by a slow‐moving‐strong TS. The strong TSs provide sufficient stirring to cause the upper layer mixing, entrainment, and upwelling, which can uplift nutrients from subsurface layer and lead to the phytoplankton blooms directly. For the TSW, the weak forcing in a short duration may not sufficiently mix the upper layer water directly. However, the wind power input in the short duration could be absorbed quickly by the ocean upper layer, resulting in strong near‐inertial oscillations (NIOs), which can support the mixing and entrainment processes in the ocean upper layer and cause the nutrient uplift. In the shelf region, the nutricline and mixed‐layer depth are shallow, which may further facilitate the formation of strong NIOs and uplift of nutrients. In analyzing the gradient Richardson number (Ri), we found Ri was correlated with the NIOs, and the Ri was below the critical value when the NIOs were strong. This result also suggests that the mixing is directly linked to the NIOs generated by TSW. Key Points: A fast‐moving weak cyclone can also trigger evident phytoplankton increase in the shallow continental shelf Storm‐induced near‐inertial oscillation as well as terrestrial discharge played vital roles in nutrient increase of the surface layer Evident phytoplankton increase after the tropical storm is also associated with the relatively shallow nutricline in the study area